The utilization of the theory of planned behavior and self-determination theory to improve physical activity following anterior cruciate ligament reconstruction - Kleis, R. R.; Hoch, M. C.; Dlugonski, D.; Hoch, J. M. (International Journal of Athletic Therapy & Training, 2022)
Patients with a history of anterior cruciate ligament reconstruction (ACLR) report decreased levels of physical activity participation, which can result in a significant public health burden. Psychosocial factors, such as fear of reinjury and decreased self-efficacy, negatively impact physical activity levels in this population. However, factors such as attitudes and beliefs toward exercise, motivation, self-efficacy, and social support are known to positively influence physical activity participation. The Theory of Planned Behavior (TPB) and Self-Determination Theory (SDT) incorporate such constructs and have been utilized to predict and improve physical activity behaviors in a variety of populations. Emerging evidence has applied the TPB and SDT to rehabilitation adherence in populations with musculoskeletal injury and post-ACLR. However, we believe a combination of the TPB and SDT will provide a framework for increasing physical activity engagement for people with a history of ACLR. The purpose of this review is to present an integrated theoretical model that combines the TPB and SDT with the aim of increasing physical activity after ACLR. Recommendations for future research and clinical practice based on the proposed model are also discussed.